Land Use Suitability Assessment in Low-Slope Hilly Regions under the Impact of Urbanization in Yunnan, China - Gui Jin; Zhaohua Li; Qiaowen Lin; Chenchen Shi; Bing Liu; Lina Yao (Advances in Meteorology)
Nowadays, the conflict between land development and land conservation has become increasingly serious in China. The plan called “town of mountain” is carried out in many nonplain areas to alleviate the conflict. To avoid geological disasters and ecological risks in those areas, land use suitability assessment is of great importance. In this paper, the fuzzy weight of evidence model is applied into land use suitability assessment in low-slope hilly regions in Yunnan, China. Fuzzy weight of evidences is calculated to determine 9 map layers. Finally, posterior probabilities are modified after synthesizing each map layer, which are used to generate a land use suitability map. The results show that 9.33%, 26.18%, 45.98%, and 18.51% of low-slope hilly regions are separately highly suitable, moderately suitable, marginally suitable, and unsuitable for development. Besides, highly and moderately suitable areas are mainly located in towns with excellent natural and socioeconomic conditions. The largest areas which are marginally suitable for development are most widely distributed. Unsuitable areas are mainly distributed far away from towns and water sources. The findings of the research will promote the rational use and scientific management of the land.